Case Report: Single Dose Anti-PD1 in a Patient With Metastatic Melanoma and Cardiac Allograft - Goodman, Amy E.; Karapetyan, Lilit; Pugliano-Mauro, Melissa; Levenson, Joshua E.; Luke, Jason J. (Frontiers in Immunology, 2021)
ABSTRACT Background: Immune-checkpoint inhibition has improved outcomes in metastatic melanoma. However, limited data describes the safety and efficacy of this treatment in the setting of cardiac allograft. Emerging translational and clinical evidence suggests that the majority of the benefit from these therapies is driven by the initial dose(s), and that attenuated dosing schedules may be as effective as continuous treatment. Case presentation: We present a case vignette of a cardiac transplant recipient with metastatic melanoma who experienced six months of clinical benefit after one dose of pembrolizumab and did not suffer allograft rejection. Conclusion: This case adds to the current available literature on the administration of checkpoint inhibitors in patients with cardiac allografts. Further, it explores potential markers of immunotherapy response and supports the potential of shorter or individualized immune-checkpoint blockade dosing strategies.